Konfigurasi Hukum Ekonomi Syariah Terhadap Siasat Dalam Jual Beli Bersyarat - Muhammad Iqbal Sanjaya (Al-Ujrah | Jurnal Ekonomi Syariah, 2023)
This paper departs from the author's academic anxiety regarding the diversity of buying and selling practices with the addition of conditions carried out by some people. The emergence of conditional buying and selling practices is based on debts, but to be able to avoid practices that are prohibited in Islam, that's why legal tactics are carried out. There are two conditional practices that the author presents, the first is conditional buying and selling practices in this case the seller has the right to be able to repurchase the goods from the buyer based on a mutually agreed upon time. The two practices are conditional buying and selling with the strategy of reselling at a cash price but below the buying and selling price carried out with a credit system. This type of research is empirical normative research, with a qualitative descriptive approach. The results in this study when viewed from the pillars of the sale and purchase contract, it can be said that they have been fulfilled. In the first case, this practice, in pure writer's opinion, was carried out on the basis of mutual assistance so that it gave birth to benefits for the parties, as reflected in the parties who made the transaction, no one was harmed. However, in the case of the second buying and selling practice it does not reflect any benefit, because the strategy in this practice is very clear that it is taking advantage of other people's circumstances to gain profit.